European buckling curves for aluminium compression members: A review of proposals for revision. Issue 3 (16th September 2019) - Misiek, Thomas; Norlin, Bert; Höglund, Torsten
ABSTRACT: As part of the ongoing revision of the Eurocodes, the regulations in EN 1999‐1‐1 on the buckling of aluminium compression members were also subjected to a critical review. This resulted in the need to revise the regulations for non‐welded compression members and for longitudinally welded compression members. The introduction of a buckling class C for soft tempers and minor adjustments in the allocation of the individual alloys and tempers to buckling classes A and B can be understood as a fundamental change. The new allocation is presented and explained. The required buckling curve for non‐welded columns made of materials of buckling class C was introduced in prEN 1999‐1‐1. In this context, minor improvements have also been made to buckling curves A and B. The curves are presented and compared with the results of numerical investigations. The comparison is done graphically as well as statistically (based on EN 1990, Annex D). For the design provisions of longitudinally welded aluminium compression members, a more extensive revision was necessary. The design concept was revised and switched to the use of separate buckling curves which are presented here. These curves are also compared with the results of numerical investigations.